Renaissance literature and its formal engagements - Rasmussen, Mark David (Palgrave Macmillan, 2002)
After theory and the new historicism, what might a self-conscious turn to formal analysis in Renaissance literary studies look like today? The essays address this question from a variety of critical perspectives, embodying a renewed engagement with questions of form.